Comparison of combined general-epidural anesthesia with general anesthesia effects on survival and cancer recurrence: a meta-analysis of retrospective and prospective studies. - Lijian Pei; Gang Tan; Lei Wang; Wenjuan Guo; Bo Xiao; Xianli Gao; Li Wang; Hong Li; Zhonghuang Xu; Xiuhua Zhang; Jing Zhao; Jie Yi; et al. (PLoS ONE, 2014)
Animals underwent combined general-epidural anesthesia (EGA) is reported to have better long-time outcome than general anesthesia (GA). This study aimed to make overall evaluation of the association between these two anesthetic techniques and prognosis of cancer patients undergoing surgery.Related databases such as PubMed and EMbase were searched for eligible studies that evaluated the influence of EGA and GA on the prognosis of cancer patients undergoing surgery. Selected studies were evaluated according to the inclusion criteria by two reviewers respectively, followed by data extraction and quality assessment. The odds ratio (OR) with their 95% confidence intervals (CIs) were calculated to assess the influence strength of EGA and GA on prognosis of cancer patients.A total of ten studies involving 3254 patients were included. The overall results demonstrated that there was no significant difference between EGA and GA group (OR = 0.88, 95% CI 0.73 to 1.06, P = 0.187) concerning postoperative recurrence and metastasis rate. In regard to the following two factors: cancer category and time of follow-up, subgroup analysis identified significant differences between EGA and GA in the group of patients with prostate cancer and the group with follow-up less than or equal to two years (OR = 0.66, 95% CI 0.46 to 0.95, P = 0.027; OR = 0.70, 95% CI 0.51 to 0.98, P = 0.035; respectively) concerning postoperative recurrence and metastasis rate. However, no significant difference was found in the group of patients with colorectal cancer (OR = 1.06, 95% CI 0.84-1.33, P = 0.62).This meta-analysis showed that EGA might be associated with improvement in prognosis of patients with operable prostate cancer and the cancer patients with follow-up less than or equal to two years. However, no obvious relationship between the improvement in prognosis of colorectal cancer and EGA were detected, comparing to GA. Furthermore, all the results should be interpreted cautiously, as heterogeneous data were used for analyzing.